2015
DOI: 10.1038/srep11629
|View full text |Cite
|
Sign up to set email alerts
|

Highly homologous proteins exert opposite biological activities by using different interaction interfaces

Abstract: We present a possible molecular basis for the opposite activity of two homologues proteins that bind similar ligands and show that this is achieved by fine-tuning of the interaction interface. The highly homologous ASPP proteins have opposite roles in regulating apoptosis: ASPP2 induces apoptosis while iASPP inhibits it. The ASPP proteins are regulated by an autoinhibitory interaction between their Ank-SH3 and Pro domains. We performed a detailed biophysical and molecular study of the Pro – Ank-SH3 interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…ASPP2 was reported to interact via its N-terminal ubiquitin-like (Ubl) domain with GTP-H-ras [ 27 ], and increase ERK phosphorylation. Phosphorylation of Ser826 in the proline-rich domain of ASPP2 by activated ERK induces ASPP2 translocation to the nucleus [ 3 ], where it interacts via its C-terminal domain with p53 to effect apoptosis [ 28 30 ]. It also mediates Ras-induced senescence by inhibiting autophagy in a p53-independent fashion [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASPP2 was reported to interact via its N-terminal ubiquitin-like (Ubl) domain with GTP-H-ras [ 27 ], and increase ERK phosphorylation. Phosphorylation of Ser826 in the proline-rich domain of ASPP2 by activated ERK induces ASPP2 translocation to the nucleus [ 3 ], where it interacts via its C-terminal domain with p53 to effect apoptosis [ 28 30 ]. It also mediates Ras-induced senescence by inhibiting autophagy in a p53-independent fashion [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with our previous findings that the N-terminus of iASPP is required for its cytoplasmic localization [ 20 ] and that phosphorylation of the N-terminal Ser84 by cyclin B1/CDK1 on iASPP disrupts iASPP dimerization [ 11 ] resulting in the exposure of the recently identified RaDAR code located at its C-terminal Ankyrin repeats, which enables its nuclear entry via the RaDAR nuclear import pathway[ 21 ]. Recently, the precise intermolecular interaction of iASPP has also been dissected by Iosub-Amir et al [ 40 ], where they show that the N-terminal iASPP peptides 60-74 and 540-562 have the strongest intermolecular interactions with the C-terminal ankyrin-repeat and SH3 domain. Our work is in keeping with this observation as caspase cleavage would remove the 60-74 residues of N-terminal iASPP important for dimerization and cytoplasmic retention, thereby facilitating its nuclear entry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, structural and biological data from Iosub-Amir et al provide an alternative explanation for the opposite biological outcomes produced by the ASPP family of proteins [ 40 ]. The intermolecular interaction of iASPP (anti-apoptotic) and ASPP2 (pro-apoptotic) are both mediated by their conserved proline-rich and ankyrin-SH3 domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,14,15 iASPP interacts with numerous apoptosis-related proteins such as the p53 protein family14 and NF-κB,16,17 mainly through its Ank–SH 3 C-terminal domains. We previously showed that the important residues for iASPP interactions with other proteins are iASPP 739–753 and iASPP 764–778 15. Recently it was shown that the Pro domain of iASPP binds the proteins Keap1 and CEP55 18,19.…”
Section: Introductionmentioning
confidence: 99%